A note on Thysananthus repletus (Lejeuneaceae: Marchantiophyta) with new report on asexual reproduction - Singh Deo, Siddhartha (Plant Science Today, 2020)
Specimens of Thysananthus repletus (Taylor) Sukkharak & Gradstein are collected and described from Alipurduar District of West Bengal in Eastern Himalaya, revealing the presence of asexual reproduction by gemmae on leaf lobe as well as on androecial and gynoecial branches, which is rare for the genus and constitutes the first such report for the species. It is also first report of occurrence of the species from the state of West Bengal. Key to the Indian species of the Thysananthus subg. Mastigolejeunea is provided.